A study for introducing a scallop freezing service in Peru through the installation of a cryogenic freezing equipment - Carlos, Alberto (2020)
This article shows the results of a research focused on the commercial and technical viability of a scallop freezing service using the individual quick freezing (IQF) method with nitrogen. The results were obtained from the identification of the project demand, service design, service engineering and economic analysis.